2009
DOI: 10.1623/hysj.54.1.160
|View full text |Cite
|
Sign up to set email alerts
|

Grid-size effects on estimation of evapotranspiration and gross primary production over a large Loess Plateau basin, China

Abstract: A distributed eco-hydrological model based on soil vegetation atmosphere transfer processes is applied to estimate actual evapotranspiration (ET) and gross primary production (GPP) over the Wuding River basin, Loess Plateau, China, based on digital elevation model, vegetation and soil information between 2000 and 2003 over three grid sizes: 250 m, 1 km and 8 km. The spatial patterns of annual ET and GPP are related to precipitation variability and land-use/cover conditions. The grid size is shown to affect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…For a specific model, the DAE on different response variables ranked differently. This is in line with Mo et al (2009), who found that the DAE on gross primary production (GPP) is more significant than that on ET. The differences could result from the different algorithms used to simulate different response variables.…”
Section: Variation Of Dae Across Production Conditions Crops Responsupporting
confidence: 90%
“…For a specific model, the DAE on different response variables ranked differently. This is in line with Mo et al (2009), who found that the DAE on gross primary production (GPP) is more significant than that on ET. The differences could result from the different algorithms used to simulate different response variables.…”
Section: Variation Of Dae Across Production Conditions Crops Responsupporting
confidence: 90%
“…, and "3 • C warming level" referred to an increase of 2.39 • C (= 3 − 0.61 • C) compared with the baseline, respectively. As large differences existed in temperature simulations among CMIP5 models and RCP scenarios, we applied a widely used time sampling method (James et al, 2017;Mohammed et al, 2017;Marx et al, 2018) to each GCM under each RCP scenario (referred to as GCM-RCP combination hereafter). A 20-year moving window, which has the same length of the baseline period, was used to determine the first period reaching a specific warming level for each combination, with the period median year referred to as the "crossing year".…”
Section: Determination Of Years Reaching Specific Warming Levelsmentioning
confidence: 99%
“…Therefore, quantitative study of the effects of elevated CO 2 concentration and increased temperature on crop physiological processes and yield has become key to addressing climate change. Several studies have related changes in agricultural phenomena such as crop yield, growth period, and water use to temperature increases (Gbetibouo and Hassan 2005;Aggarwal et al 2006a,b;Dhungana et al 2006;Tao et al 2003Tao et al , 2008bChallinor and Wheeler 2008;Mo et al 2009;Challinor et al 2010;Laux et al 2010;Liu and Yuan 2010;Rotter et al 2011;Tao and Zhang 2011).…”
Section: Introductionmentioning
confidence: 99%